1996
DOI: 10.1006/viro.1996.0017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subtle Changes in the SU Protein of Ecotropic Murine Leukemia Virus on Its Brain Capillary Endothelial Cell Tropism and Interference Properties

Abstract: PVC-211 murine leukemia virus (MuLV) is a neuropathogenic variant of Friend MuLV (F-MuLV) that causes a rapidly progressive neurodegenerative disease in susceptible rodents. PVC-211 MuLV, but not the parental F-MuLV, can infect rat brain capillary endothelial cells (BCEC) efficiently, and the major determinant for BCEC tropism of PVC-211 MuLV is localized within the XbaI-BamHI fragment of the viral genome containing the 5' half of the env gene. To further dissect the XbaI-BamHI region for its effects on BCEC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…Neuropathogenic PVC-211 MuLV and its nonneuropathogenic variant PVFe5 MuLV were grown in Rat-1 or NIH 3T3 fibroblasts in Dulbecco's minimal essential medium (DMEM) plus 10% fetal calf serum (FCS) as previously described (31). Virus samples were collected after 24-h incubation of cells with fresh medium and stored at Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathogenic PVC-211 MuLV and its nonneuropathogenic variant PVFe5 MuLV were grown in Rat-1 or NIH 3T3 fibroblasts in Dulbecco's minimal essential medium (DMEM) plus 10% fetal calf serum (FCS) as previously described (31). Virus samples were collected after 24-h incubation of cells with fresh medium and stored at Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies using chimeras between PVC-211 MuLV and F-MuLV demonstrated that infection of BCEC is a prerequisite for neurodegeneration induced by PVC-211 MuLV (32). Further studies attributed the ability of PVC-211 MuLV to efficiently infect BCEC to two amino acid changes in the receptor binding domain of its envelope protein (31), which creates a unique heparin binding domain that may allow the virus to bind to proteoglycans on the surface of BCEC (22), aiding infection of this difficult-to-infect cell type. These results suggested that neurodegeneration caused by PVC-211 MuLV is an indirect result of virus infection of blood vessels within the CNS.…”
mentioning
confidence: 99%
“…Stromal cell line MC3T3-G2/PA6 (PA6) (13) was provided by Kevin Holmes and maintained in ␣-minimal essential medium supplemented with 10% FCS. A primary culture of rat brain capillary endothelial cells was prepared and kept as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Neuropathogenic PVC-211 and PVF-e5 MuLV, a nonneuropathogenic variant of PVC-211, were grown in NIH 3T3 cells as described previously (30). The viral supernatants had titers of 10 5 to 10 6 PFU/ml as determined by an XC assay (40).…”
Section: Methodsmentioning
confidence: 99%
“…The determinant of the BCEC tropism of PVC-211 MuLV was mapped to two amino acids (G 116 and K 129 ) which lie within the putative receptor binding domain of the envelope surface glycoprotein (SU) (30). Within the CNS, reactive astrocytes and degenerating neurons showed no evidence of virus infection (19).…”
mentioning
confidence: 99%